Embedding S=1/2 Kagome-like lattice in reduced graphene oxide - Gupta, Kriti; Jha, Plawan Kumar; Dadwal, Arun; Debnath, Anil K.; Jaiswal, Ishan; Rana, Shammi; Joy, Pattayil A.; Ballav, Nirmalya (Journal of Physical Chemistry Letters, 2019)
An elegant platform to explore frustrated magnetism is the kagome spin lattice. In this work, clinoatacamite, a naturally occurring S = 1/2 kagome-like antiferromagnetic insulator, is synthesized in water at ambient pressure for the first time from a cuprous chloride (CuCl) precursor whereby Cu(I) was spontaneously oxidized to Cu(II) in the form of clinoatacamite [Cu-2(OH)(3)Cl] with a simultaneous reduction of graphene oxide (GO) to reduced graphene oxide (rGO) in one pot. A stable nanocomposite of phase-pure clinoatacamite nanocrystals embedded in the rGO matrix was isolated. The clinoatacamite-rGO nanocomposite was determined to be magnetically active with a markedly enhanced coercive field of similar to 2500 Oe at S K as well as electronically active with a conductivity value of similar to 200 S.m(-1) at 300 K. Our results illustrate an avenue of combining exotic magnetic and electronic lattices without impeding their individual characteristics and synergistically generating a new class of magnetic semiconductors.